TTTCA Repeat Expansion of SAMD12 in a New Benign Adult Familial Myoclonic Epilepsy Pedigree - Liu, Chaorong; Song, Yanmin; Yuan, Ying; Peng, Ying; Pang, Nan; Duan, Ranhui; Huang, Wen; Qin, Xuehui; Xiao, Wenbiao; Long, Hongyu; Huang, Sha; Zhou, Pinting; et al. (Frontiers in Neurology, 2020)
Benign adult familial myoclonic epilepsy (BAFME) is an autosomal dominant disorder characterized by adult-onset cortical myoclonus with or without seizures. Recently, it was reported to be associated with intronic TTTTA/TTTCA expansions. To investigate whether these abnormal expansions are involved in our new pedigree from China, whole exome sequencing (WES) and repeat-primed polymerase chain reaction (RP-PCR) analysis were performed to detect potential mutation in pedigree members. Neither causal mutations cosegregated with the disease in the family nor any novel mutation was identified through WES, while an abnormal TTTCA expansion in SAMD12 was identified by RP-PCR and then proved to be cosegregated in the pedigree. All the 12 alive affected individuals (M/F = 4/8; average age = 46.7 years old, range from 27 to 66) showed typical characteristics of BAFME. In addition, maternal clinical anticipation was observed in six mother/child pairs. In conclusion, our study offered the evidence of intronic pentanucleotide expansions in SAMD12 from a new Chinese BAFME pedigree, which further confirmed the association between this expansion and the pathogenesis of BAFME.